On the first Baryonychinae (Theropoda, Spinosauridae) teeth from South America - Lacerda, Mauro B.s.; Aragão, Paulo R.l.; Vieira, Fabiana S.; Sales, Marcos A.f.; Liparini, Alexandre (Zootaxa, 2023)
We report the first occurrence in South America of spinosaurid specimens belonging to the clade Baryonychinae. The material comprises three tooth crowns recovered from the Lower Cretaceous (Berriasian–Valanginian) of the Feliz Deserto Formation, State of Sergipe, northeast Brazil. The three specimens have the typical conidont condition, displaying a fluted morphology, veined enamel texture and carinae extending to the cervix region, conditions similar to those shared among spinosaurid theropods. Furthermore, a notable feature is the presence of a serrated carinae composed of 6–7 diminutive denticles per millimetre, a key feature shared by baryonychine spinosaurids. Phylogenetic and multivariate analyses performed on dentition-based and crown-based datasets of theropod taxa confirm the relationship of the three tooth crowns described here with the well-supported spinosaurid clade. Our results retrieve the taxa which comprise the “classically” baryonychine clade as individual branches within a polytomy which includes the three tooth crowns and a subclade of spinosaurines (Spinosaurus + Angaturama/Irritator). Additionally, the discriminant and cluster analyses suggest that the materials are more similar to Suchomimus than to Baryonyx morphometrically, but clearly bearing similarities with baryonychines (sharing a similar morphospace). These new findings paleogeographically expand the occurrence of this clade to western Gondwana, and comprise one of the oldest spinosaurid records worldwide, which brings implications on hypotheses for the emergence and evolution of the clade. Furthermore, these new records indicate the presence of more than one spinosaurid taxon in the Lower Cretaceous deltaic paleoenvironment of the Feliz Deserto Formation.